Adenosine, methacholine, and exercise challenges in children with asthma or paediatric chronic obstructive pulmonary disease. Issue 5 (May 1995) - Avital, A; Springer, C; Bar-Yishay, E; Godfrey, S
Abstract : BACKGROUND--Bronchial hyperreactivity to methacholine is present in children with asthma and other types of paediatric chronic obstructive pulmonary disease (COPD), while hyperreactivity to exercise is more specific for asthma. Adenosine 5'-monophosphate (AMP) is a potent bronchoconstrictor and, like exercise, may provoke asthma by activating mast cells. This study investigated the suitability of AMP as a specific challenge for asthma in children. METHODS--Bronchial provocation challenges with methacholine and AMP were performed in a double blind fashion using tidal breathing in 51 children with asthma, 21 with paediatric COPD of various types, and in 19 control children. Each subject also underwent a standardised exercise challenge after inhalation challenges were completed. Sensitivity and specificity curves were constructed and the intersection point of sensitivity and specificity for each type of challenge was determined. RESULTS--When the asthmatic patients were compared with the children with COPD, the intersection points for AMP, exercise and methacholine were 90%, 85%, and 50%, respectively. When compared with the controls the same intersection points were 98%, 84%, and 92%, and when children with paediatric COPD were compared with controls they were 55%, 50%, and 82%. CONCLUSIONS--Methacholine distinguishes both asthma and paediatric COPD from controls with a sensitivity of 82-92%, but does not distinguish between asthma and paediatric COPD; exercise and AMP distinguish asthma from controls with a sensitivity and specificity of 84-98% but they also distinguish asthma from paediatric COPD with a sensitivity and specificity of 85-90%. AMP inhalation is a practical aid for diagnosing asthma and distinguishing it from COPD in children of all ages.